A Conjunction Of Sn-2 Fatty Acids And Overall Fatty Acid Composition Combined With Chemometric Techniques Increase The Effectiveness Of Lard Detection In Fish Fee - Mohd Sukri Hassan; Mohamed Haniff Hanafy Idris; Yanty Noorzianna Manaf; Mohd Nasir Mohd Desa; Amalia Mohd Hashim; Muhamad Shirwan Abdullah Sani; Nor Nadiha Mohd Zaki; Mohd Hafis Yuswan; Mohd Salleh Kamaruddin; Yus Aniza Yusof; Shuhaimi Mustafa (Elsevier B.V., 2024)
Indexed by WOS/SCOPUS/ERA